Immune thrombocytopenia: Effectiveness of frontline steroids and comparison of azathioprine, splenectomy, and rituximab as second‐line treatment. (31st August 2018) - Chang, Hung; Tang, Tzung‐Chih; Hung, Yu‐Shin; Li, Pei‐Ling; Kuo, Ming‐Chung; Wu, Jin‐Hou; Wang, Po‐Nan
Abstract: Objective: For immune thrombocytopenia (ITP), efficacy of frontline steroids is well established. However, clinical data comparing various treatment options for refractory or relapsed ITP are limited. We aimed to investigate the outcome of frontline steroid treatment for ITP patients and compare common second‐line modalities in a single institute in Taiwan. Methods: We collected the complete outpatient list over a 6‐month period. Patients were identified from the list, and medical records were reviewed to capture the data retrospectively. The diagnosis of ITP was made by excluding other etiologies. Results: Among 665 patients with thrombocytopenia, the diagnosis of ITP was made in 375. Two hundred and fifty‐seven patients (51 males, median age 45.5) received treatment. Response to steroids was evaluable for 184 patients. Complete response (CR) was achieved in 120 (65.2%) and partial response in 43 (23.3%). In 21 (11.4%) patients, ITP was refractory to steroids. Among those with CR, 76 (63%) patients relapsed in a median of 9.5 months. After relapse or steroid failure, 57 (49%) received azathioprine treatment and 38 (32%) underwent splenectomy. Response rate was 71.4% (38.1% CR) for azathioprine and 91.4% (77.1% CR) for splenectomy. Rituximab was effective in 8 of 10 patients. Conclusion: Steroids are effective frontline treatment for ITP, but relapse is common. Both azathioprine and splenectomy are effective treatment after steroid failure. Rituximab appears to a reasonable second‐line treatment option in our limited experience.